Portraits of Parthian king: rock-reliefs and the mountain fortresses of Rabana-Merquly in Iraqi Kurdistan - Brown, Michael; Miglus, Peter A.; Rasheed, Kamal; Ahmad, Mustafa (Iraq, 2018)
This article presents detailed illustrations of two rock-reliefs from the neighbouring sites Rabana and Merquly, located on the flanks of Mt. Piramagrun in Iraqi Kurdistan. Both matching sculptures are aligned with perimeter fortifications that enclose substantial architectural remains. Based on numismatic parallels, supported by archaeological evidence, it is proposed that these depictions of near life-size figures represent an anonymous Arsacid King of Kings from the early first millennium (c. a.d. 50-150), who was credited with construction of the mountain fortresses. Rabana and Merquly together form an important landscape of settlement on the north-western frontier of the Parthian Empire.
Gesehen am 25.10.2019